Mineralogical attenuation processes associated with the evolution of acid mine drainage in sulfide-rich mine wastes - Valente, Teresa Maria Fernandes (2019)
The geochemical evolution of acid mine drainage results in secondary minerals that play a key role in the environmental behavior of the mine wastes. The present work is focused on these newly formed minerals at the Penedono waste dump, characterized by fine-grained tails with pyrite and arsenopyrite. Mineralogical study led to an inventory of secondary phases, comprising soluble sulfates, scorodite, and oxyhydroxysulfates. In addition, there is amorphous Fe, As rich-nanoprecipitates. Jarosite and scorodite are abundant minerals, acting as cement for encrusting tails in Fe and As-rich hardpans. These hard structures are relatively insoluble, retaining toxic elements, thereby contributing to natural attenuation of mining contamination associated with the sulphide wastes.